Long-term outcome of a patient with paradoxical hypertrichosis after laser epilation. (3rd April 2018) - Honeybrook, Adam; Crossing, Tascha; Bernstein, Eric; Bloom, Jason; Woodward, Julie
ABSTRACT: One underreported, rare side effect of laser hair removal is paradoxical hypertrichosis. It is largely unknown what the long-term outcomes are of patients who develop this complication. We report a 21-year-old, Fitzpatrick II, male patient, who had patchy areas of dark hair affecting various body areas. An Alexandrite 755 nm laser was used to address the desired areas at energies between 20 and 22 J/cm 2 at 10–12-week intervals over a course of seven treatments. After three treatments, the patient noted a significant increase in the density and length of hairs involving the back, shoulders, neck, and upper arms. The patient was followed on a biannual basis, without further epilatory intervention. After 10 years, the areas of paradoxical hair growth were sparser compared to immediate post-treatment but remained denser compared to pre-treatment. This case illustrates improvement in the condition over time without intervention. Further studies are needed to determine the etiopathogenesis of this phenomenon.